Tutankhamun’s collar: Repeated reconstructions of a single collar - Ekstedt Bjersing, Marie (FormAkademisk, 2021)
The aim of this paper is to discuss what happens when repeating a reconstruction of the same textile. The author of this article is also the craftsperson that made the four reconstructions presented. The original collar reconstructed belonged to Tutankhamun. The collar is circular, woven in a circle. Before the reconstructions, this method of weaving circular shapes had not been described. The first reconstruction focused on the collar. Fifteen years later, three additional reconstructions were made. This time, the focus was to reconstruct the craft, by the use of fewer, simpler tools. Parallel to practical work there was an exploration of how to make documentation. One conclusion in the project is when changing focus from reconstructing a textile to reconstructing a craft, more similarity to the original was achieved.